Positive psychology interventions during pregnancy: A systematic review - Tharunnia M.S Ganesan; Zuhrah Beevi; Alan J. Gow; Guek Nee Ke (Applied Psychology: Health and Well-Being, 2026)
Abstract Positive psychology interventions (PPI) have been applied and demonstrated evidence in various population groups. The present systematic review focused on the types and influence of PPI on the physical and psychological health of pregnant women. Studies that matched the selection criteria were identified on EBSCOhost, PsychINFO, Web of Science, PubMed, Scopus and four positive psychology journals. From the 2528 records identified, finally eight studies were included in the review. PPI in this review were delivered utilising various positive psychology components such as hope, gratitude and optimism based on existing theories, for example, the strengths theory, broaden‐and‐build theory, and hope theory. Most interventions were conducted from 14 gestational weeks onwards and were delivered via virtual platforms or mobile applications. As a result of this systematic review, it was identified that PPIs for maternal well‐being were aimed at improving (1) physical health, including labour pain, nausea and vomiting; (2) psychological health, including stress, emotions, anxiety and depression; and (3) subjective health, including life satisfaction, perceived social support and quality of life. Most of the selected studies provided significant evidence towards improvement of well‐being outcomes from administering PPI. For future studies, in‐depth PPI integrated coping and support approaches should be further evidenced among diverse pregnant populations.